Physical Properties and Fast Neutron Remove Cross Section of PbO-MgO-Bi2O3-B2O3 Glasses - Hawwa M. Asmaial; Zeinab Algadhi; Seham Y. M. Dogharsham; Hend A. Saltani; Ibrahim M. hammamu; Daefalla M. Tawati (African Journal of Advanced Pure and Applied Sciences, 2025)
This study analyzed the physical parameters of xPbO-10MgO-25Bi₂O₃-(65-x) B₂O₃ glasses with x values of 5, 10, 15, 20, 25, and 30 mol%, including density of glass (ρg), volume of molar (VM), molar volume of oxygen (VO), oxygen packing density (OPD), Poisson’s rate (σ), oxygen ions (NO-ions) and lead ions concentration (Npb-ions). As PbO concentration increases in the matrix of glass, the density, volume of molar, molar volume of oxygen, and Npb-ions increase. Conversely, as the concentration of PbO increases, OPD and NO-ions decrease. The Poisson’s rate values suggest a strengthening of the binding within the matrix of glass. Furthermore, to examine the glass material as a shield against fast neutrons, the effective removal cross-section for fast neutrons (FNRCS or )was computed theoretically. Based on the information obtained, it has been reported that the incorporation of lead oxide enhanced the physical properties of the glass samples, which exhibited greater shielding efficiency against fast neutrons compared to various materials.